Evaluación de la calidad de energía eléctrica suministrada por la subestación Lasso a la empresa aglomerados Cotopaxi s.a. en el año 2014. Propuesta de un plan correctivo energéticamente eficiente - Vizuete Alcocer, Alejandro Hernán (2016)
It has become imperative in the industrial field continuous improvement in all areas in order to optimize resources and improve productivity, for this reason they have been automated industrial processes by installing power electronics equipment with non-linear loads that cause variations in the wave form. This present work has as objective to evaluate the aspects of quality of electric power supplied by Electric company Provincial Cotopaxi S.A. to the Company Aglomerados Cotopaxi S.A. to verify the compliance with the standards established by IEC 61000-4 and Regulation No. 004/01 CONELEC, based on measurements made with an energy analyzer at the delivery point (point 1) and point PADMOUNTED transformer output (point 2). It is proposed to install voltage regulators and passive filters for correction of voltage levels and power factor, It is evaluated the impact on the harmonics, flicker and generally on the quality of electricity.